2004
DOI: 10.1183/09031936.04.00016103
|View full text |Cite
|
Sign up to set email alerts
|

Brief adrenomedullin inhalation leads to sustained reduction of pulmonary artery pressure

Abstract: The effect of aerosolised adrenomedullin (ADM), a potent vasodilator peptide, on pulmonary artery pressure was studied for 24 h in a surfactant-depleted piglet model. Animals received either aerosolised ADM (50 ng?kg -1 ?min -1 , ADM, n=6), or aerosolised normal saline solution (control, n=6). Aerosol therapy was performed for a 2 h treatment period followed by a 22 h observation period. Ventilator settings were adapted to keep arterial oxygen tension and carbon dioxide arterial tension between 13.3-14.6 kPa a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
8
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
3
8
0
2
Order By: Relevance
“…Interestingly, the adrenomedullin-linked amelioration in pulmonary hypertension was accompanied by a 30% reduction in interleukin (IL)-1b gene expression in lung tissue [13]. In agreement with VAN DER VARDT et al [13], other investigators have reported an anti-inflammatory property of adrenomedullin.…”
supporting
confidence: 59%
See 3 more Smart Citations
“…Interestingly, the adrenomedullin-linked amelioration in pulmonary hypertension was accompanied by a 30% reduction in interleukin (IL)-1b gene expression in lung tissue [13]. In agreement with VAN DER VARDT et al [13], other investigators have reported an anti-inflammatory property of adrenomedullin.…”
supporting
confidence: 59%
“…Another interesting and important finding by VON DER HARDT et al [13] is the observation that aerosolisation of adrenomedullin reduced endothelin (ET)-1 mRNA in lung tissue and ET-1 protein expression in endothelial cells of pulmonary arteries. Since ET-1 is a potent pulmonary vasoconstrictor, implicated in a broad spectrum of pulmonary disorders associated with pulmonary hypertension [18], adrenomedullin inhalation seems to be a goal-directed approach in this setting.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, AM has recently been given by inhalation in tests of its potential benefit in PH. With this method of administration, AM led to sustained and selective reduction of pulmonary artery pressure in a surfactant-depleted piglet model (145) and in rats with monocrotaline-induced PH (88) and improved pulmonary hemodynamics and exercise tolerance in patients with IPAH (87).…”
Section: )mentioning
confidence: 99%